Preparation method of high-purity titanium dioxide for batteries

By improving the pretreatment and hydrolysis process of titanium slag, combined with strong magnetic iron removal and calcining steps, the problem of insufficient impurity removal rate in the prior art was solved, and titanium dioxide with high purity and high specific surface area was prepared to meet the requirements of battery use. .

CN119284944APending Publication Date: 2025-01-10GUANGXI JINMAO TITANIUM

Patent Information

Application Number
CN202411278197.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the prior art, there is no improvement in the preparation method of the added seed crystal preparation and optimization process to improve the impurity removal rate, resulting in the purity and specific surface area of ​​the titanium dioxide being insufficient to meet the requirements of battery use.

Method used

After grinding and alkali calcining, impurities are leached through sulfuric acid in two steps, acid dissolution and strong magnetization iron removal, oxalic acid and complexing agent are added for hydrolysis, followed by multiple water washing and calcination, and finally obtained by using a strong magnetization iron removal machine. High purity titanium dioxide.

Benefits of technology

The purity and specific surface area of ​​titanium dioxide are significantly improved. The prepared titanium dioxide has high purity and high specific surface area, which is suitable for battery applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040861430000031
    Figure BDA0005040861430000031
  • Figure BDA0005040861430000111
    Figure BDA0005040861430000111
Patent Text Reader

Abstract

The invention belongs to the technical field of battery material production, and particularly relates to a preparation method of high-purity titanium dioxide for batteries. The invention aims to provide a preparation method of high-purity titanium dioxide for a battery. The preparation method is used for solving the technical problem that the impurity removal rate is not increased by improving a preparation method of an additional seed crystal and optimizing procedures in the prior art. The titanium slag is used as a raw material, a metatitanic acid crude product is obtained after alkali baking pretreatment, acidolysis and hydrolysis, redundant impurities are removed through subsequent procedures, and the high-purity titanium dioxide for the battery is obtained. The titanium slag subjected to alkali roasting treatment is changed in component structure, the concentration and temperature of sulfuric acid required by acidolysis are greatly reduced, oxalic acid and a complexing agent are added in the hydrolysis process to hydrolyze titanium ions to form metatitanic acid, the purity of the metatitanic acid is greatly improved, seed crystals prepared through ultrasonic treatment are added, and the prepared metatitanic acid can be calcined at a low temperature to form rutile type titanium dioxide. The prepared titanium dioxide has high purity and relatively high specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery material production, and specifically relates to a method for preparing high-purity titanium dioxide for batteries. Background Art

[0002] Titanium dioxide is commonly known as titanium dioxide. Titanium dioxide is an important inorganic chemical product. It is non-toxic, odorless, has high chemical stability and excellent optical properties, and is widely used in coatings, papermaking, cosmetics, electronics and other fields. High-purity titanium dioxide has the properties of a semiconductor, and its conductivity increases rapidly with the rise in temperature. Titanium dioxide for batteries requires high purity and a high specific surface area. my country is rich in titanium resources, but the grade of titanium ore is low, and the content of impurities such as calcium and magnesium is high. Half of the titanium resources are in the form of isomorphous vanadium-titanium magnetite, which is difficult to use. Therefore, it is necessary to smelt to form titanium slag before using it to extract titanium dioxide.

[0003] Patent CN108178187A discloses a lithium titanate battery negative electrode material titanium dioxide and a preparation method thereof. The method comprises the following steps: titanium slag and titanium ore are subjected to acid hydrolysis, aging and leaching to obtain titanium liquid A, hot filtration, and concentration of the clear titanium liquid to obtain titanium liquid B, seed crystals are added, and hydrolysis is performed to obtain hydrolyzed metatitanic acid, and then washed, bleached, rinsed, and washed in sequence, and then classified, filtered, flash evaporated, and crushed to obtain titanium dioxide, a negative electrode material for lithium titanate batteries. The titanium dioxide prepared by this method has the advantages of high specific surface area and low impurity content, but the existing method does not solve the technical problem of improving the preparation method of adding external seed crystals and optimizing the process to improve the impurity removal rate. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing high-purity titanium dioxide for batteries, which is used to solve the technical problem that the prior art has not improved the preparation method of adding external crystal seeds and optimized the process to improve the impurity removal rate.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing high-purity titanium dioxide for batteries comprises the following steps:

[0007] S1, grinding titanium slag and mixing it with alkali, roasting it at high temperature, leaching impurities with sulfuric acid in two steps, filtering and collecting the solid phase to obtain pretreated titanium slag;

[0008] S2, adding sulfuric acid to the pretreated titanium slag for acid hydrolysis, and using a strong magnetic iron remover to remove impurities and filter solid impurities to obtain titanium liquid;

[0009] S3, adding oxalic acid and a complexing agent to the titanium liquid, mixing with an external seed crystal, and hydrolyzing to obtain a crude metatitanic acid product;

[0010] S4, washing the crude metatitanic acid product with water once, adding sulfuric acid and trivalent titanium solution for bleaching, and obtaining a metatitanic acid semi-finished product after rinsing;

[0011] S5, beating the semi-finished product of titanic acid, adding ammonia water to adjust the pH, and then washing it twice to obtain a finished product of titanic acid;

[0012] S6, calcining the metatitanic acid product;

[0013] S7. After calcination, use a strong magnetic iron remover to remove impurities, and then grind to obtain high-purity titanium dioxide.

[0014] Preferably, the method for preparing the external seed crystals comprises the following steps:

[0015] S11, dilute a portion of the titanium liquid to obtain a mixed solution A, preheat the mixed solution A and the sodium hydroxide solution to 85-90° C., dropwise add the mixed solution A to the sodium hydroxide solution while stirring, to obtain a mixed solution B;

[0016] S12, raising the temperature of the mixed solution B to 95-97°C within 2-3 minutes, then keeping the temperature, and ultrasonically treating for 1-5 minutes;

[0017] S13, measuring the stability of the titanium liquid while performing ultrasonic treatment at a heat preservation state, and when the stability value reaches 110-130, the seed crystal is prepared.

[0018] Preferably, in S11, the amount of the partial titanium liquid is 1 to 10% of the total mass of the titanium liquid;

[0019] Preferably, in S11, the concentration of the mixed solution A is 80-120 g / L (in terms of TiO2), the stability is not less than 100, the concentration of sodium hydroxide is 10±0.2%, and the alkali-titanium ratio (ratio of sodium hydroxide content to titanium dioxide content) is 16-20%;

[0020] Preferably, in S12, the frequency used for ultrasonic treatment is 20-30 kHz, and the ultrasonic amplitude range is 30-50%;

[0021] Preferably, in S13, in order to prevent the stability of the seed crystal from decreasing, the seed crystal needs to be used within 20 minutes after being prepared;

[0022] As a preferred method, the test method for the stability of titanium liquid is as follows:

[0023] Take 1 mL of titanium liquid in a container, add deionized water at room temperature and stir continuously until the solution just becomes turbid. Record the total volume of deionized water from the time the solution is added to the time the solution just becomes turbid. The stability is calculated as follows:

[0024]

[0025] Where S-titanium liquid stability;

[0026] V 水 -Total volume of deionized water from the time the solution was added until the solution just became turbid, mL;

[0027] V 钛液 -Volume of titanium liquid added, mL.

[0028] Preferably, in S1, the titanium slag is placed in a crusher and ground until the particle size of the titanium slag is less than 40 μm;

[0029] Preferably, in S1, the alkali is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, etc., preferably, the alkali is sodium carbonate, the mass ratio of sodium carbonate to titanium slag is 1:2.3-3, and the alkali is calcined at 850-900°C for 2-3h;

[0030] Preferably, in S1, the leaching temperature is 80-90°C, the mass ratio of titanium slag to sulfuric acid is 1:8-10, the sulfuric acid concentration in the first step is 13-17%, and the leaching is 1-2h; the sulfuric acid concentration in the second step is 23-27%, and the leaching is 1.5-2.5h, and the magnesium and calcium contents in the treated titanium slag are less than 0.9%, and the iron content is less than 1.1%;

[0031] Preferably, in the S2, the concentration of sulfuric acid is 40-60%, the mass ratio of titanium slag to sulfuric acid is 1:4-7, and the acid hydrolysis is carried out at 85-95°C for 2-3h, and the acid hydrolysis rate is 96-97%;

[0032] Preferably, in S2, solid impurities are removed by filtration at 25-60°C, the concentration of the titanium liquid is controlled at 180-210 g / L (in terms of TiO2), the stability is not less than 550, and the iron content is less than 5 g / L; the strong magnetic iron remover controls the magnetic field to be 550-580 kA / m;

[0033] Preferably, in S3, the concentration of oxalic acid is 8-10%, and the volume ratio of oxalic acid added to titanium liquid is 0.1-0.3:1; the complexing agent is one or more of ethylenediaminetetraacetic acid, sodium dodecylbenzenesulfonate, sodium sulfite, etc., and the molar ratio of the complexing agent added to the iron content in the titanium liquid is 4-5:1;

[0034] Preferably, in S3, the titanium liquid is preheated to 94-96° C. after adding oxalic acid and a complexing agent, and the seed crystal is added and stirred continuously, and the temperature is kept for 10-30 minutes and then raised to boiling. After the titanium liquid turns gray, the heating and stirring are stopped immediately, and the temperature is kept constant for 20-40 minutes. After the aging is completed, stirring is continued, and the temperature is raised to boiling and kept at a slightly boiling state for 3-3.5 hours, and then the hydrolysis reaction is completed;

[0035] Preferably, in S4, the crude metatitanic acid is washed once with dilute sulfuric acid of pH=1, washed with a leaf filter at a water temperature of 55-65°C and a vacuum degree of 0.05MPa≤0.1MPa for 2-4h, and after the iron content is controlled below 300ppm, the slurry is adjusted to a concentration of 260-300g / L of titanium content;

[0036] Preferably, in S4, the added trivalent titanium solution is prepared from metatitanic acid and aluminum powder, the trivalent titanium concentration of the slurry is controlled at 0.7-1.7 g / L, the sulfuric acid concentration is 98%, the amount of sulfuric acid added is 15-25% of the titanium content of the slurry, and the rinsing is carried out at 0.05 MPa≤vacuum degree≤0.1 MPa for 2-4 hours, and the iron content of the metatitanic acid semi-finished product is controlled below 70 ppm;

[0037] Preferably, in S5, the semi-finished product of metatitanic acid is slurried to a concentration of 260-300 g / L titanium content, an ammonia concentration of 10-20%, the pH is adjusted to 6-8, and washed for 2-4 hours, and the iron content of the metatitanic acid product is controlled below 20 ppm;

[0038] Preferably, in S6, the calcination temperature is controlled at 750-900°C, and the calcination time is controlled at 1.5-2.5h;

[0039] Preferably, in S7, the grinding and crushing is performed until D50 is 0.9-1.1 μm and D90 is 2.3-4 μm, and the strong magnetic iron remover is used to control the magnetic field to 550-580 kA / m for impurity removal.

[0040] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0041] 1. The present invention uses titanium slag as a raw material, obtains metatitanic acid after alkaline roasting pretreatment, acidolysis and hydrolysis, washes the metatitanic acid with water, bleaches and calcines it, and uses a strong magnetic iron remover to remove excess impurities after acidolysis and calcination to obtain high-purity titanium dioxide for batteries. The composition structure of the titanium slag after alkaline roasting treatment is changed, and the surface becomes a loose porous structure. The sulfuric acid concentration and temperature required for acidolysis are greatly reduced. The addition of oxalic acid and a complexing agent during the hydrolysis process not only inhibits the oxidation of ferrous ions to ferric ions, but also forms a stable complex with ferric ions to inhibit the formation of ferric hydroxide precipitation by ferric ions, thereby greatly improving the purity of metatitanic acid formed by hydrolysis of titanium ions. The addition of seed crystals prepared by ultrasonic treatment enables the prepared metatitanic acid to be calcined at a lower temperature to form rutile titanium dioxide. The prepared titanium dioxide has high purity and a high specific surface area.

[0042] 2. The present invention adds crystal seeds prepared with the assistance of ultrasound during the hydrolysis of titanium liquid, which not only accelerates the hydrolysis process, but also the crystal seeds prepared by this method have high activity and can reduce the calcination temperature of preparing rutile titanium dioxide without the participation of calcined crystal seeds. The prepared titanium dioxide has a higher specific surface area.

[0043] 3. The addition of oxalic acid during the hydrolysis of titanium liquid in the present invention can inhibit the oxidation of ferrous ions, and can complex iron ions with the complexing agent to inhibit the hydrolysis of iron ions to form precipitation, promote the hydrolysis of titanium ions, and improve the purity of metatitanic acid, thereby making the subsequent impurity removal more thorough. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1: This example discloses a method for preparing high-purity titanium dioxide for batteries, comprising the following steps:

[0046] S1. Grind 2 kg of titanium slag to 38 μm and mix with 0.67 kg of sodium carbonate, roast at 900 ° C for 2 h, and leach with sulfuric acid. The first step is a sulfuric acid concentration of 17%, leaching for 1 h, and the second step is a sulfuric acid concentration of 27%, leaching for 1.5 h. The mass ratio of titanium slag to sulfuric acid is 1:10, and the leaching temperature is 90 ° C. Filter and collect the solid phase to obtain the pretreated titanium slag;

[0047] S2, take 1.8kg of pretreated titanium slag, add 7.2kg of 60% sulfuric acid, and then acid hydrolyze at 85°C for 3h, use a strong magnetic iron remover to remove impurities under a magnetic field of 560kA / m, filter solid impurities at 60°C to obtain titanium liquid, the concentration of the titanium liquid is controlled at 210g / L (in terms of TiO2), the stability is 650, and the iron content is 5g / L;

[0048] S3, take 5L of titanium liquid, add 1.5L of 10% oxalic acid and 652.3g of ethylenediammonium tetraacetic acid, preheat to 96°C, add seed crystals and stir continuously, keep warm for 10min and then heat to boiling, stop heating and stirring immediately after the titanium liquid turns gray, keep at constant temperature for 20min, continue stirring after the aging, heat to boiling and keep at a slightly boiling state for 3h, then the hydrolysis reaction ends and the crude metatitanic acid is prepared;

[0049] S4, the crude metatitanic acid is washed once with dilute sulfuric acid of pH=1, washed with a leaf filter at a water temperature of 65°C and a vacuum degree of 0.05MPa≤≤0.1MPa for 2h, the iron content after the first washing is 275ppm, the slurry is adjusted to a concentration of 300g / L of titanium content, and then bleached with 98% sulfuric acid and a trivalent titanium solution prepared from metatitanic acid and aluminum powder, the trivalent titanium concentration of the slurry is controlled at 1.7g / L, the amount of sulfuric acid added is 25% of the titanium content of the slurry, and rinsed at 0.05MPa≤vacuum degree≤0.1MPa for 2-4h to obtain a metatitanic acid semi-finished product, the iron content of the metatitanic acid semi-finished product is 55ppm;

[0050] S5, beating the semi-finished product of metatitanic acid to a concentration of 300 g / L of titanium content, adding 20% ​​ammonia water to adjust the pH to 8, and then washing twice for 2 to 4 hours to obtain a fine product of metatitanic acid, the iron content of which is 18 ppm;

[0051] S6, calcining the metatitanic acid product at a temperature of 900°C for 1.5 hours;

[0052] S7. After calcination, use a strong magnetic iron remover to remove impurities, control the magnetic field to 580kA / m, and then grind it. Use a ball mill to grind it to D50 of 1.1μm and D90 of 4μm to obtain high-purity titanium dioxide.

[0053] The preparation method of the added seed crystal comprises the following steps:

[0054] S11, dilute 10 mL of 210 g / L titanium liquid to 120 g / L (in terms of TiO2) of mixed solution A, preheat the mixed solution A and a 10.2% sodium hydroxide solution to 90° C., then dropwise add the mixed solution A into the sodium hydroxide solution, with an alkali-titanium ratio (ratio of sodium hydroxide content to titanium dioxide content) of 20%, and stir while dropping to obtain a mixed solution B;

[0055] S12, raising the temperature of the mixed solution B to 97°C within 3 minutes, then keeping the temperature, and treating with ultrasound for 5 minutes;

[0056] S13. The stability of the titanium liquid is measured while the ultrasonic treatment is performed at a temperature of 30 kHz and an ultrasonic amplitude range of 50%. When the stability value reaches 130, a seed crystal is prepared.

[0057] Example 2: This example discloses a method for preparing high-purity titanium dioxide for batteries, comprising the following steps:

[0058] S1. Grind 2 kg of titanium slag to 20 μm and mix with 0.86 kg of sodium carbonate, roast at 850 ° C for 3 h, and leach with sulfuric acid. The first step is 13% sulfuric acid concentration, leaching for 2 h, the second step is 23% sulfuric acid concentration, leaching for 2.5 h, the mass ratio of titanium slag to sulfuric acid is 1:8, the leaching temperature is 80 ° C, and the solid phase is collected by filtration to obtain the pretreated titanium slag;

[0059] S2, take 1.8kg of pretreated titanium slag, add 12.6kg of 40% sulfuric acid, and acid hydrolyze at 95°C for 2h, use a strong magnetic iron remover to remove impurities under a magnetic field of 570kA / m, filter solid impurities at 25°C to obtain titanium liquid, the concentration of the titanium liquid is controlled at 180g / L (in terms of TiO2), the stability is 550, and the iron content is 2g / L;

[0060] S3, take 5L of titanium liquid, add 0.5L of 8% oxalic acid and 208.7g of ethylenediammonium tetraacetic acid, preheat to 94°C, add seed crystals and stir continuously, keep warm for 30min and then heat to boiling, stop heating and stirring immediately after the titanium liquid turns gray, keep at constant temperature for 40min, continue stirring after the aging, heat to boiling and keep at a slightly boiling state for 3.5h, then the hydrolysis reaction ends and the crude metatitanic acid is prepared;

[0061] S4, the crude metatitanic acid is washed once with dilute sulfuric acid of pH=1, washed with a leaf filter at a water temperature of 55°C and a vacuum degree of 0.05MPa≤≤0.1MPa for 4h, the iron content after the first washing is 175ppm, the slurry is adjusted to a concentration of titanium content of 260g / L, and then bleached by adding 98% sulfuric acid and a trivalent titanium solution prepared from metatitanic acid and aluminum powder, the trivalent titanium concentration of the slurry is controlled at 0.7g / L, the amount of sulfuric acid added is 15% of the titanium content of the slurry, and rinsed at 0.05MPa≤vacuum degree≤0.1MPa for 4h to obtain a metatitanic acid semi-finished product, the iron content of the metatitanic acid semi-finished product is 30ppm;

[0062] S5, beating the semi-finished product of metatitanic acid to a concentration of 260 g / L of titanium content, adding 10% ammonia water to adjust the pH to 6, and then washing twice for 4 hours to obtain a fine product of metatitanic acid, the iron content of which is 10 ppm;

[0063] S6, calcining the metatitanic acid product at a temperature of 750°C for 2.5 hours;

[0064] S7. After calcination, use a strong magnetic iron remover to remove impurities, control the magnetic field to 550kA / m, and then grind it. Use a ball mill to grind it to D50 of 0.9μm and D90 of 2.3μm to obtain high-purity titanium dioxide.

[0065] The preparation method of the added seed crystal comprises the following steps:

[0066] S11, taking 100 mL of 180 g / L titanium liquid and diluting it into 80 g / L (in terms of TiO2) of mixed solution A, preheating the mixed solution A and a 9.8% sodium hydroxide solution to 85° C., and then dropping the mixed solution A into the sodium hydroxide solution, with an alkali-titanium ratio (ratio of sodium hydroxide content to titanium dioxide content) of 16%, and stirring while dropping to obtain a mixed solution B;

[0067] S12, raising the temperature of the mixed solution B to 95°C within 2 minutes, then keeping the temperature, and treating with ultrasound for 1 minute;

[0068] S13. The stability of the titanium liquid is measured while the ultrasonic treatment is performed at a temperature preservation condition. The frequency used for the ultrasonic treatment is 20 kHz, and the ultrasonic amplitude range is 30%. When the stability value reaches 110, the seed crystal is prepared.

[0069] Example 3: This example discloses a method for preparing high-purity titanium dioxide for batteries, comprising the following steps:

[0070] S1. Grind 2 kg of titanium slag to 30 μm and mix with 0.8 kg of sodium carbonate, roast at 870°C for 2.5 h, and leach with sulfuric acid. The first step is a sulfuric acid concentration of 15%, leaching for 1.5 h, the second step is a sulfuric acid concentration of 25%, leaching for 2 h, the mass ratio of titanium slag to sulfuric acid is 1:9, the leaching temperature is 85°C, and the solid phase is collected by filtration to obtain the pretreated titanium slag;

[0071] S2, take 1.8kg of pretreated titanium slag, add 9kg of 50% sulfuric acid, and then acid hydrolyze at 90°C for 2.5h, use a strong magnetic iron remover to remove impurities under a magnetic field of 576kA / m after acid hydrolysis, filter solid impurities at 55°C to obtain titanium liquid, the concentration of the titanium liquid is controlled at 200g / L (in terms of TiO2), the stability is 570, and the iron content is 1g / L;

[0072] S3, take 5L of titanium liquid, add 1L of 9% oxalic acid and 117.4g of ethylenediammonium tetraacetic acid, and preheat to 95°C, add seed crystals and stir continuously, keep warm for 20min, and then heat to boiling. Stop heating and stirring immediately after the titanium liquid turns gray, and keep at a constant temperature for 30min. After the aging, continue stirring, heat to boiling and keep at a slightly boiling state for 3.5h, and then the hydrolysis reaction ends to prepare a crude metatitanic acid product;

[0073] S4, the crude metatitanic acid is washed once with dilute sulfuric acid of pH=1, washed with a leaf filter at a water temperature of 55°C and a vacuum degree of 0.05MPa≤≤0.1MPa for 3h, the iron content after the first washing is 130ppm, the slurry is adjusted to a concentration of titanium content of 280g / L, and then bleached by adding 98% sulfuric acid and a trivalent titanium solution prepared from metatitanic acid and aluminum powder, the trivalent titanium concentration of the slurry is controlled at 1g / L, the amount of sulfuric acid added is 20% of the titanium content of the slurry, and rinsed for 3h at a vacuum degree of 0.05MPa≤≤0.1MPa to obtain a metatitanic acid semi-finished product, the iron content of the metatitanic acid semi-finished product is 20ppm;

[0074] S5, beating the semi-finished product of metatitanic acid to a concentration of 280 g / L of titanium content, adding 15% ammonia water to adjust the pH to 7, and then washing twice for 3 hours to obtain a fine product of metatitanic acid, the iron content of which is 9 ppm;

[0075] S6, calcining the metatitanic acid product at a temperature of 850°C for 2 hours;

[0076] S7. After calcination, use a strong magnetic iron remover to remove impurities, control the magnetic field to 570kA / m, and then grind it. Use a ball mill to grind it to D50 of 1μm and D90 of 3μm to obtain high-purity titanium dioxide.

[0077] The preparation method of the added seed crystal comprises the following steps:

[0078] S11, take 50mL of 200g / L titanium liquid and dilute it to 100g / L (in terms of TiO2) mixed solution A, preheat the mixed solution A and 10% sodium hydroxide solution to 87°C, then add the mixed solution A dropwise to the sodium hydroxide solution, the alkali-titanium ratio (ratio of sodium hydroxide content to titanium dioxide content) being 18%, and stir while adding dropwise to obtain mixed solution B;

[0079] S12, raising the temperature of the mixed solution B to 96°C within 2.5 minutes, then keeping the temperature, and treating with ultrasound for 4 minutes;

[0080] S13, while conducting ultrasonic treatment at a heat preservation condition, measuring the stability of the titanium liquid, the frequency used for the ultrasonic treatment is 25 kHz, the ultrasonic amplitude range is 40%, and when the stability value reaches 120, the seed crystal is prepared.

[0081] Comparative Example 1

[0082] The difference between this comparative example and Example 1 is that the roasting time in the titanium slag pretreatment is changed to 1 hour, in the sulfuric acid leaching process, the sulfuric acid concentration in the first step is changed to 40%, the sulfuric acid concentration in the second step is 60%, and the leaching temperature is changed to 99°C.

[0083] Comparative Example 2

[0084] The difference between this comparative example and Example 1 is that 30% of the original titanium liquid is used for preparing the seed crystals, and after the seed crystals are added to the titanium liquid, the micro-boiling state time during the hydrolysis process is prolonged to 6 hours.

[0085] Comparative Example 3

[0086] The difference between this comparative example and Example 1 is that the order of adding the complexing agent is changed to adding it during the water washing process to remove impurities.

[0087] Comparative Example 4

[0088] The difference between this comparative example and Example 1 is that during the calcination process, the temperature is changed to 1100° C. and the calcination time is changed to 4 h.

[0089] Comparative Example 5

[0090] The difference between this comparative example and Example 1 is that the magnetic field of the strong magnetic iron remover for removing impurities is changed to 400 kA / m.

[0091] Experimental example

[0092] The appearance, purity, specific surface area and iron content of the titanium dioxide prepared in Examples 1-3 and Comparative Examples 1-5 were measured. The appearance was manually observed, and the purity, specific surface area and iron content were measured by commercially available testing equipment. The test results are shown in the following table:

[0093]

[0094] It can be seen from the above table that the titanium dioxide obtained in Examples 1 to 3 has high purity, low iron content, and high specific surface area, which meets the requirements of battery production. The titanium dioxide obtained in Comparative Example 1 is reddish in color and has a high iron content. The reason is that the calcination is insufficient in the titanium slag treatment stage, and the impurities are still combined with the titanium solid. The change in the sulfuric acid concentration and leaching time for leaching impurities not only causes a large amount of impurities to remain in the titanium slag, but also causes a significant loss of titanium content in the titanium slag, resulting in insufficient subsequent impurity removal of the product, and the product hue is red, which does not meet the requirements of battery production; the purity and specific surface area of ​​Comparative Example 2 are reduced, and the reason is that the mass of titanium liquid used for hydrolysis is too much and the hydrolysis time is too long, resulting in the formation of metatitanic acid with too large particle size and serious agglomeration, and too many other impurities. Even if some agglomerations are removed through subsequent process treatment, its specific surface area is still significantly reduced. It does not meet the requirements of battery production; in Comparative Example 3, a chelating agent is used in the water washing stage. Since there is no chelating agent involved in the hydrolysis stage, the iron content in titanic acid is relatively high. In the water washing stage, the chelating agent chelates the iron ions and is adsorbed by the titanic acid particles, which are difficult to be removed by water washing. A large amount of water remains on the surface of the titanic acid during filtration. Insufficient filtration causes other impurities and iron content in the product to increase significantly, resulting in a decrease in product purity, a light red appearance, and a decrease in specific surface area; in Comparative Example 4, the calcination temperature is too high and the calcination time is too long, resulting in serious compaction of the product and the subsequent treatment cannot remove impurities that are too tightly combined with the product, resulting in a decrease in the specific surface area of ​​the product and a decrease in purity; in Comparative Example 5, the magnetic field is too small to adsorb iron impurities, and a certain amount of titanium content is lost through the iron removal opportunity, which instead causes a decrease in product purity and an increase in iron content.

[0095] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0096] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing high-purity titanium dioxide for batteries, characterized in that: The following steps are involved: S1, grinding titanium slag and mixing it with alkali, roasting it at high temperature, leaching impurities with sulfuric acid in two steps, filtering and collecting the solid phase to obtain pretreated titanium slag; S2, adding sulfuric acid to the pretreated titanium slag for acid hydrolysis, using a strong magnetic iron remover to remove impurities after acid hydrolysis, and filtering solid impurities to obtain titanium liquid; S3, adding oxalic acid and a complexing agent to the titanium liquid, mixing with an external seed crystal, and hydrolyzing to obtain a crude metatitanic acid product; S4, washing the crude metatitanic acid product with water once, adding sulfuric acid and trivalent titanium solution for bleaching, and obtaining a metatitanic acid semi-finished product after rinsing; S5, beating the semi-finished product of metatitanic acid, adding ammonia water to adjust the pH, and then washing it twice to obtain a fine product of metatitanic acid; S6, calcining the metatitanic acid product; S7. After calcination, use a strong magnetic iron remover to remove impurities, and then grind to obtain high-purity titanium dioxide.

2. The method for preparing high-purity titanium dioxide for battery according to claim 1, characterized in that: The preparation method of the external seed crystal comprises the following steps: S11, dilute a portion of the titanium liquid to obtain a mixed solution A, preheat the mixed solution A and the sodium hydroxide solution to 85-90° C., dropwise add the mixed solution A to the sodium hydroxide solution while stirring, to obtain a mixed solution B; S12, raising the temperature of the mixed solution B to 95-97°C within 2-3 minutes, then keeping the temperature, and ultrasonically treating for 1-5 minutes; S13, measuring the stability of the titanium liquid while performing ultrasonic treatment at a heat preservation state, and when the stability value reaches 110-130, the seed crystal is prepared.

3. The method for preparing high-purity titanium dioxide for battery according to claim 2, characterized in that: In the S11, the amount of part of the titanium liquid is 1-10% of the total mass of the titanium liquid, the concentration of the mixed liquid A is 80-120 g / L in terms of TiO2, the stability is not less than 100, the concentration of sodium hydroxide is 10±0.2%, and the ratio of sodium hydroxide content to titanium dioxide content is 16-20%; in the S12, the frequency used for ultrasonic treatment is 20-30 kHz, and the ultrasonic amplitude range is 30-50%; in the S13, in order to prevent the stability of the seed crystal from decreasing, the seed crystal must be used within 20 minutes after preparation.

4. The method for preparing high-purity titanium dioxide for battery according to claim 1, characterized in that: In S1, the titanium slag is placed in a crusher and ground until the particle size of the titanium slag is less than 40μm. The alkali is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, etc. Preferably, the alkali is sodium carbonate. The mass ratio of sodium carbonate to titanium slag is 1:2.3-3. The slag is roasted at 850-900°C for 2-3h, and the leaching temperature is 80-90°C. The mass ratio of titanium slag to sulfuric acid is 1:8-10. The concentration of sulfuric acid in the first step is 13-17%, and the leaching is 1-2h; the concentration of sulfuric acid in the second step is 23-27%, and the leaching is 1.5-2.5h. The magnesium and calcium contents in the treated titanium slag are less than 0.9%, and the iron content is less than 1.1%.

5. The method for preparing high-purity titanium dioxide for battery according to claim 1, characterized in that: In the S2, the sulfuric acid concentration is 40-60%, the mass ratio of titanium slag to sulfuric acid is 1:4-7, acid hydrolysis is carried out at 85-95°C for 2-3h, the acid hydrolysis rate is 96-97%, and solid impurities are removed by filtration at 25-60°C. The concentration of the titanium liquid is controlled at 180-210g / L in terms of TiO2, the stability is not less than 550, and the iron content is less than 5g / L; the strong magnetic iron remover controls the magnetic field to be 550-580kA / m.

6. The method for preparing high-purity titanium dioxide for battery according to claim 1, characterized in that: In the S3, the concentration of oxalic acid is 8-10%, the volume ratio of oxalic acid added to titanium liquid is 0.1-0.3:1, the complexing agent is one or more of ethylenediammonium tetraacetic acid, sodium dodecylbenzenesulfonate, sodium sulfite, etc., and the molar ratio of the complexing agent added to the iron content in the titanium liquid is 4-5:

1. After the oxalic acid and the complexing agent are added to the titanium liquid, it is preheated to 94-96°C, and after the seed crystals are added, it is stirred continuously, kept warm for 10-30 minutes, and then heated to boiling. After the titanium liquid turns gray, heating and stirring are stopped immediately, and it is matured at a constant temperature for 20-40 minutes. After the maturity is completed, stirring is continued, and after the temperature is heated to boiling, it is kept in a slightly boiling state for 3-3.5 hours before the hydrolysis reaction ends.

7. The method for preparing high-purity titanium dioxide for battery according to claim 1, characterized in that: In the S4, the crude metatitanic acid is washed once with dilute sulfuric acid of pH=1, and washed for 2-4 hours with a leaf filter at a water temperature of 55-65°C and a vacuum degree of 0.05MPa≤0.1MPa. After the iron content is controlled below 300ppm, the slurry is adjusted to a concentration of 260-300g / L of titanium content. The added trivalent titanium solution is prepared from metatitanic acid and aluminum powder, and the trivalent titanium concentration of the slurry is controlled to be 0.7-1.7g / L, and the sulfuric acid concentration is 98%, the amount of sulfuric acid added is 15-25% of the titanium content of the slurry, and the rinsing is carried out for 2-4 hours at a vacuum degree of 0.05MPa≤≤0.1MPa, and the iron content of the semi-finished titanate product is controlled below 70ppm; in S5, the semi-finished titanate product is slurried to a concentration of 260-300g / L of titanium content, an ammonia concentration of 10-20%, the pH is adjusted to 6-8, and washed for 2-4 hours, and the iron content of the finished titanate product is controlled below 20ppm.

8. The method for preparing high-purity titanium dioxide for battery according to claim 1, characterized in that: In the S6, the calcination temperature is controlled at 750-900°C, and the calcination time is controlled at 1.5-2.5h; in the S7, the slurry is ground to a D50 of 0.9-1.1μm and a D90 of 2.3-4μm, and the strong magnetic iron remover is used to remove impurities under a magnetic field of 550-580kA / m.

Citation Information

Patent Citations

  • Lithium titanate battery anode material titanium dioxide and preparation method thereof

    CN108178187A

Cited By

  • Method for removing metal impurity ions in titanium dioxide primary product

    CN120794003A

  • Preparation method for producing titanium dioxide from titanium liquid with poor clarity and titanium dioxide

    CN121361828A

  • Titanium-silicon composite resin heavy metal adsorption material and preparation method thereof

    CN122912826A